Influence of free ferrite on the mechanical properties of high strength intercritical Austempered Ductile Iron - A. D. Basso; M. Caldera; N. E. Tenaglia; D. O. Fernandino; R. E. Boeri (Fracture and Structural Integrity)
The first stage of this study investigates the precipitation of free ferrite from the austenite on fully austenitized ductile iron. Several sets of samples of low alloy ductile iron are fully austenitized and then cooled down to different temperatures and different times within the intercritical austenite-ferrite-graphite phase field. Based on these results, heat treatment cycles aimed at obtaining microstructures composed of free ferrite and ausferrite are carried out. Tensile, impact and toughness tests are performed to characterize the mechanical properties. The results show that, related to the high strength austempered ductile iron grades, the best combinations of properties were obtained from the mixed structures composed of 5% free ferrite and 95% ausferrite, resulting from the austempering at 280C. These amounts of free ferrite allow obtaining an increase of the elongation (about 50%) and impact toughness (about 10%) while the tensile strength and fracture toughness decrease by about 1.5 and 15% respectively